2018
DOI: 10.1158/1535-7163.mct-18-0186
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of Aurora Kinases with AMG 900 Exhibits Potent Preclinical Activity Against Acute Myeloid Leukemia with Distinct Post-Mitotic Outcomes

Abstract: Aurora kinase A and B have essential and non-overlapping roles in mitosis, with elevated expression in a subset of human cancers, including acute myeloid leukemia (AML). In this study, pan-aurora kinase inhibitor (AKI) AMG 900 distinguishes itself as an anti-leukemic agent that is more uniformly potent against a panel of AML cell lines than are isoform-selective AKIs and classic AML drugs. AMG 900 inhibited AML cell growth by inducing polyploidization and/or apoptosis. AMG 900 and aurora-B selective inhibitor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Reports have shown that AMG900 inhibited the growth of glioblastoma cells in vitro ultimately leading to cell cycle arrest and senescence [ 135 ]. In MOLM-13 AML cell line, treatment with AMG900 was linked to inhibition of histone H3 phosphorylation, polyploidy and increased apoptosis with the upregulation of p53 [ 136 ]. The IC50 concentrations of AMG900 on breast cancer cell lines are shown in Table S1 [ 137 ].…”
Section: Targeting Aurkb In Cancermentioning
confidence: 99%
“…Reports have shown that AMG900 inhibited the growth of glioblastoma cells in vitro ultimately leading to cell cycle arrest and senescence [ 135 ]. In MOLM-13 AML cell line, treatment with AMG900 was linked to inhibition of histone H3 phosphorylation, polyploidy and increased apoptosis with the upregulation of p53 [ 136 ]. The IC50 concentrations of AMG900 on breast cancer cell lines are shown in Table S1 [ 137 ].…”
Section: Targeting Aurkb In Cancermentioning
confidence: 99%
“…Among these, sorafenib (I), the 1,4-disubstituted phthalazine derivatives, vatalanib (II), AAC789 (III), AMG 900 (IV), and IM-023911 (V) revealed potent inhibitory activity against VEGFR-2 in nanomolar levels of IC 50 . [12,13] Sorafenib is an FDA-approved antiangiogenic drug that shares the above pharmacophoric features. [14] The phthalazine ring is a vital pharmacophoric scaffold present in the core structures of many anticancer molecules [11,[15][16][17][18][19] with potent activity against hepatocellular carcinoma, [18] colon cancer, [11] and breast cancer, [19] and as degraders of VEGFR-2.…”
Section: Introductionmentioning
confidence: 99%
“…Several Aurora kinase inhibitors have progressed through preclinical testing and into phase I or phase II trials, including Aurora A (MLN8237, MK-5108, ENMD-2076 [130], the latter also targeting other kinases), Aurora B (AZD-1152 and AZD-2811), and a number of dual or pan-Aurora inhibitors (AS703569/MSC1992371A [131], MK-0457, AT9283, GSK1070916 [132], AMG 900 [133], PHA-739358). However, few drugs reached advanced clinical phase development in acute leukemias, due to low activity and/or intolerability of a significant patient proportion to the required dose.…”
Section: Introductionmentioning
confidence: 99%